(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
Although the phenomenon of the hiring of Swiss troops conducted by European states in the second half of the Fifteenth century is very well known to modern historiography – also owing to its political and diplomatic implications – not much has been written about the Swiss companies operating in Italy at the end of the century. In this paper, the attentive study of the Registro degli Assoldamenti a truppe tedesche, 1495-1499 – conserved in the State Archive of Milan – resulted in a close-up analysis of the Swiss companies hired by Ludovico il Moro, pointing out their military and organisational aspects: the role of the captains, the hierarchy and the different figures of the officers, the esprit de corps typical of these companies and their relations with the ducal administration relatively to the payments and the negotiation of the condotte. Moreover, the Registro enabled us to investigate the human dimension of these companies, giving us information about the geographical and family origin of many captains, several of which has been identified. Finally, through the Registro, light has been shed on the methods used by the duchy to keep Swiss companies under control, especially in such turbulent times as the end of the Fifteenth century.